KONSEP PERENCANAAN DALAM PENDIDIKAN ISLAM: SEBUAH STUDI LITERATUR - Fitrilioni, Fitrilioni; Lesmana, Inda; Yuriszulmi, Yuriszulmi; Nengsih, Ratna; Hendrizal, Hendrizal (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to describe the concept of planning in education using literature studies. The method used in this research is a qualitative method with a literature study approach. The results of this research show that educational planning is the basis for implementing activities in education by looking at the future to develop education so that it can be more effective and efficient in accordance with community needs to achieve educational development targets, so that the goals of education can also be realized according to expectations. Apart from that, in Islam, educational planning starts from the preparation, practical and evaluation stages.